2000
DOI: 10.1089/152460900318498
|View full text |Cite
|
Sign up to set email alerts
|

Tubal Sterilization and Use of an IUD and Risk of Cervical Cancer

Abstract: The relationship of tubal sterilization and use of an intrauterine device (IUD) to the risk of invasive squamous cell cervical cancer was evaluated in a case-control study carried out in Shandong, China, from 1989 to 1991. Patients (cases) were 272 women aged 30-77 years with newly diagnosed invasive squamous cell cervical cancer in Shandong Province Tumor Hospital. Controls were 893 randomly selected screened women matched to the cases by age (within 2 years) and county. A decrease in risk was observed in use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…As expected, cervical smear screening was shown in this study to reduce the risk of both HPV-16 and HPV-18 tumor types. The reduced risk in women who had used an IUD likely represents an effect of screening at the time of IUD insertion or removal, a phenomenon also reported from China (44).…”
Section: Discussionmentioning
confidence: 80%
“…As expected, cervical smear screening was shown in this study to reduce the risk of both HPV-16 and HPV-18 tumor types. The reduced risk in women who had used an IUD likely represents an effect of screening at the time of IUD insertion or removal, a phenomenon also reported from China (44).…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies have shown a decreased risk for cervical cancer among intrauterine device users [Li et al, 2000;Hammouda et al, 2005;Castellsague et al, 2006]. Castellsague et al [2006] found a lower risk for cervical adenocarcinomas even after adjustment for HPV status and screening history, and Hammouda et al [2005] and Li et al [2000] observed that the protective effect of intrauterine devices was even greater in long-term users. A single study showed that intrauterine device users had an increased clearance rate of HPV 18 [Munoz et al, 2009].…”
Section: Discussionmentioning
confidence: 88%
“…In a Chinese study 15 , IUCD use was associated with a decreased risk of cervical carcinoma attributed mainly to the frequent Pap smear examinations in this population. British authors 16 reported a higher prevalence of cervical intraepithelial neoplasia among IUCD users as compared to non-users, and they too demanded further investigation.…”
Section: Discussionmentioning
confidence: 82%